The Late Jurassic pterosaur Rhamphorhynchus, a frequent victim of the ganoid fish Aspidorhynchus? - Eberhard Frey (Public Library of Science (PLoS), 2012)
Associations of large vertebrates are exceedingly rare in the Late Jurassic Solnhofen Limestone of Bavaria, Southern Germany. However, there are five specimens of medium-sized pterosaur Rhamphorhynchus that lie adjacent to the rostrum of a large individual of the ganoid fish Aspidorhynchus. In one of these, a small leptolepidid fish is still sticking in the esophagus of the pterosaur and its stomach is full of fish debris. This suggests that the Rhamphorhynchus was seized during or immediately after a successful hunt. According to the fossil record, Rhamphorhynchus frequently were accidentally seized by large Aspidorhnychus. In some cases the fibrous tissue of the wing membrane got entangled with the rostral teeth such that the fish was unable to get rid of the pterosaur. Such encounters ended fatally for both. Intestinal contents of Aspidorhynchus-type fishes are known and mostly comprise fishes and in one single case a Homoeosaurus. Obviously Rhamphorhynchus did not belong to the prey spectrum of Aspidorhynchus.